2018
DOI: 10.1080/19768354.2018.1528175
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of inflammatory responses in the early development of calcific aortic valve disease: lessons from statin therapy

Abstract: Calcific aortic valve disease (CAVD) is the most common degenerative heart valve disease. Among the many risk factors for this disease are age, hypercholesterolemia, hypertension, smoking, type-2 diabetes, rheumatic fever, and chronic kidney disease. Since many of these overlap with risk factors for atherosclerosis, the molecular and cellular mechanisms of CAVD development have been presumed to be similar to those for atherogenesis. Thus, attempts have been made to evaluate the therapeutic efficacy of statins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 99 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…To date, researchers have attempted to elucidate the molecular pathologic mechanism of AS by investigating the roles of immune cell infiltration and resident cells, such as VICs and valvular endothelial cells (VECs), in the disease's progression. 12 , 13 , 14 , 15 These cells have been the focus of research because macrophages and T lymphocytes are major contributors to inflammation, whereas VICs function in calcification and fibrosis during disease progression. In one example, Oba and colleagues 16 found a greater distribution of CD163-positive macrophages in calcified AVs than that in noncalcified AVs and showed that the infiltrating CD163-positive macrophages were expressing high levels of bone morphogenetic protein 2.…”
Section: Discussionmentioning
confidence: 99%
“…To date, researchers have attempted to elucidate the molecular pathologic mechanism of AS by investigating the roles of immune cell infiltration and resident cells, such as VICs and valvular endothelial cells (VECs), in the disease's progression. 12 , 13 , 14 , 15 These cells have been the focus of research because macrophages and T lymphocytes are major contributors to inflammation, whereas VICs function in calcification and fibrosis during disease progression. In one example, Oba and colleagues 16 found a greater distribution of CD163-positive macrophages in calcified AVs than that in noncalcified AVs and showed that the infiltrating CD163-positive macrophages were expressing high levels of bone morphogenetic protein 2.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b is another intriguing cytokine involved in the valve calcification process. Its levels are indeed increased in the stenotic aortic valve, making IL-1b subject to numerous research studies in the last decade (Isoda et al, 2010;Nadlonek et al, 2013;Lee and Choi, 2018). The IL-1b enhances the expression of matrix metalloproteinases (MMPs), a group of enzymes responsible for the degradation of extracellular matrix proteins.…”
Section: Innate Response In Cavdmentioning
confidence: 99%
“…The calcified aortic valve disease (CAVD) is a primary valve disease that negatively affects a high number of people worldwide ( Kirchhof et al, 2016 ). A variety of factors are involved in CAVD development, but it appears that inflammatory factors play a pivotal role ( Lee and Choi, 2018 ). The nuclear factor-kappaB (NF-κB) is suggested to induce inflammation ( Sinjari et al, 2019 ).…”
Section: Curcumin and Molecular Pathways And Mechanismsmentioning
confidence: 99%